Leonardo da Vinci - Stanley, Diane (New York : Morrow Junior Books, 1996)
A biography of the Italian Renaissance artist and inventor who, at about age thirty, began writing his famous notebooks which contain the outpourings of his amazing mind.
Includes bibliographical references
NC1010L
Keywords: Leonardo -- 1452-1519 -- Criticism and interpretation -- Juvenile literature; Artists